2018
DOI: 10.3892/br.2018.1176
|View full text |Cite
|
Sign up to set email alerts
|

Influence of GnRH antagonist in reproductive women on in�vitro fertilization and embryo transfer in fresh cycles

Abstract: The aim of the present study was to evaluate the influence of a gonadotropin-releasing hormone (GnRH) antagonist compared with a GnRH agonist on in vitro fertilization (IVF) cycle outcome in reproductive women. The characteristics of treatment and outcomes of pregnancy were retrospectively compared between the antagonist (GnRH-A, antagonist group) and agonist (GnRH-a, agonist group) regimens. The area under the curve (AUC) of receiver operating characteristic (ROC) curves was also used to evaluate whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…A total of 51 (1.7%) out of 2972 patients experienced OHSS with mild (0.8%), moderate (0.3%) or severe (0.6%) intensity. A similar incidence of OHSS (1.21%) was reported in a recent retrospective study with Chinese women treated with a GnRH antagonist protocol [30]. The freeze-all policy was implemented as a prevention of OHSS in 14.9% of patients who presented signs, symptoms or risk of OHSS.…”
Section: Discussionsupporting
confidence: 68%
“…A total of 51 (1.7%) out of 2972 patients experienced OHSS with mild (0.8%), moderate (0.3%) or severe (0.6%) intensity. A similar incidence of OHSS (1.21%) was reported in a recent retrospective study with Chinese women treated with a GnRH antagonist protocol [30]. The freeze-all policy was implemented as a prevention of OHSS in 14.9% of patients who presented signs, symptoms or risk of OHSS.…”
Section: Discussionsupporting
confidence: 68%
“…In our study, we found lower treatment time and pharmaceutical use in the GnRH-antagonist protocol. This protocol has therefore become widespread and is an indispensable part of ovarian stimulation in IVF due to lower risk of ovarian hyperstimulation syndrome (OHSS) and its function as preventing premature luteinization, which is essential for normal follicular development and oocyte maturation [40]. For pituitary desensitization, both daily administration of GnRHagonist and immediately blocking the secretion of LH with GnRH-antagonist can effectively block premature LH surges.…”
Section: Discussionmentioning
confidence: 99%
“…What needs to be verified is whether acupuncture can improve the success rate of IVF. erefore, the IVF scheme should be unified relatively, because different IVF schemes, such as different follicular induction schemes, have different pregnancy rates [27].…”
Section: Future Directionsmentioning
confidence: 99%